To the Occiput or Not? C1–C2 Ligamentous Laxity in Children with Down Syndrome - Siemionow, Kris; Chou, Dean (Evidence-Based Spine-Care Journal, 2014)
Study Design Retrospective case review.Objective Atlantoaxial instability with and without basilar invagination poses a considerable challenge in management regarding reduction, surgical approach, decompression, instrumentation choice, and extent of fusion. A variety of strategies have been described to reduce and stabilize cranial settling with basilar invagination. Modern instrumentation options included extension to the occiput, C1–C2 transarticular fixation, and C1 lateral mass–C2 pars among others. Since not all cases of cranial settling are the same, their treatment strategies also differ. Factors such as local vascular anatomy, amount of subluxation, need for distraction, and shape of occipital condyles will dictate level and type of instrumentation. The objective of this study was to outline treatment options and provide a rationale for the surgical plan.Methods Two cases of C1–C2 instability in patients with Down syndrome are described. Case 2 underwent C1–C2 instrumented fusion, whereas case 1 involved posterior instrumented fusion to the occiput.Results Both patients tolerated the procedures well. There were no complications. Minimum follow-up was 1 year. There was no loss of reduction. Solid arthrodesis was achieved in both cases.Conclusion Successful reduction can be achieved with both C1–C2 instrumented fusion as well as O–C instrument fusion. Factors such as local vascular anatomy, amount of subluxation, need for distraction, and shape of occipital condyles will dictate level and type of instrumentation.
Keywords: C1–C2 instability; basilar invagination; Down syndrome; pediatric; occiput; os odontoideum